Study of Factors Determining Outcomes in the Hospitalized Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (COPD) - Sijapati, MJ; Bhatta, N; Khanal, B; Lamsal, M; Chaudhary, S (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of mortality and morbidity across the world. Information related to the factors associated with COPD exacerbation and factors determining outcome in hospitalized patient with acute exacerbation of COPD are very important for effective long-term management of this disease. Within this background we attempted to study the factors determining outcome in hospitalized patients with acute exacerbation of COPD. METHODS: The study was prospective observational study. Hundred consecutive patients hospitalized with acute exacerbation of COPD were prospectively assessed. RESULTS: Patients required mechanical ventilation and Intensive Care Unit (ICU) transfer were 17 (17%). Patients with hypercapnia pCO2 [(80.24 ± 10.76mmHg P=0.001], pH [(7.24 ± 0.062) P=0.004] with type 2 respiratory failure required ICU transfers with mechanical ventilatory support and these variables were statistically significant in univariate analysis. Patients who were in COPD stage III (FEV1/FVC ratio < 0.35) and having the poor arterial blood gas parameters pH (7.24±0.02) P=0.001, pCO2 [(76.5±13.12mmHg,P=0.006] had bad prognosis. The patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) who were smokers and exposed to indoor air pollution due to use of biomass fuels had poor outcomes. CONCLUSION: Patients with AECOPD hospitalized in a tertiary care center in a developing country suggest that FEV1/FVC impairment, decreased pH, increased pC02, current smoking status and presence of biomass exposure are associated with prolonged hospitalization, ICU admission and death. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11171 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 28-34